The Grand Challenge To Reinvent Computing A new World Model of Computing - Hartenstein, Reiner (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2010)
Computers are very important for all of us. But brute force disruptive architectural developments in industry and threatening unaffordable operation cost by excessive power consumption are a massive future survival problem for our existing cyber infrastructures, which we must not surrender. The impact is a fascinating challenge to reach new horizons of research in computer science. We need a new generation of talented innovative scientists and engineers to start the beginning second history of computing. This paper introduces its new world model.